Tiny thoughts on anger - Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
Feeling angry is normal, but Rita gives us an example of how she learned to handle that emotion appropriately
Education
1
Keywords: Educational psychology